A Novel Validated Method to Determine the Relationship Between Insulation Thickness and the Annual Cooling Cost in Desert Climates - Mohamed A. Makawi; Wahhaj Ahmed; Habibelrahman Sherif Kenawy; Ahmed Abd El Fattah (Applied Sciences)
Energy-efficient building envelope design is essential for minimizing cooling loads and reducing energy consumption, particularly in hot desert climates. This study presents a model that optimizes insulation thickness by taking into account climate-specific conditions and economic factors. The model employs a life-cycle cost analysis framework, incorporating energy savings, insulation costs, and payback periods across various climatic zones. A typical wall is considered with three commonly applied insulation materials. The optimization is validated by energy modeling. A key contribution of this study is the introduction of a correction factor based on average humidity for each city, which adjusts the conduction-based model to account for latent heat effects from moisture-dependent insulation degradation. Unlike existing building codes, which prescribe fixed insulation requirements regardless of regional climate conditions, our approach dynamically adapts insulation thickness based on Cooling Degree Days (CDDs) and economic feasibility. The results reveal significant variations in optimal insulation thickness across different cities, demonstrating the necessity of climate-responsive insulation strategies. The analysis indicates that locations with higher CDD, such as Jeddah and Dhahran, require thicker insulation to reduce cooling loads effectively, whereas cities with lower cooling demand, such as Khamis Mushait, necessitate thinner insulation for economic viability. The results show that polystyrene (K = 0.034 W/m.K) has the least cost, whereas polyurethane (K = 0.24 W/m.K) records the least thickness in Saudi Arabia. This study presents a model that optimizes insulation thickness by taking into account climate-specific conditions and economic factors.